Association of the platelet-to-high-density lipoprotein cholesterol ratio (PHR) with metabolic syndrome and metabolic overweight/obesity phenotypes: A study based on the Dryad database - Chuncheng Wu; Ziyi Hu; Ping Zhang (PLoS ONE, 2025)
Background Overweight/obesity and metabolic syndrome (MetS) are major global public health challenges. The platelet-to-high-density lipoprotein cholesterol ratio (PHR) has emerged as a potential biomarker reflecting both inflammatory status and lipid metabolism; however, its association with MetS and metabolic overweight/obesity phenotypes is not well understood. The present study aims to investigate the association of the PHR with MetS and metabolic overweight/obesity phenotypes. Methods We derived data from the Dryad data repository. This retrospective study included 1,592 physical examination participants in Wuhan Union Hospital from 2020 to 2021. Based on BMI categories and metabolic status, we defined and distinguished four metabolic overweight/obesity phenotypes: metabolically healthy with normal weight (MHNW), metabolically unhealthy with normal weight (MUNW), metabolically healthy with overweight/obesity (MHO), and metabolically unhealthy with overweight/obesity (MUO). PHR was calculated as the ratio of platelets to HDL cholesterol. Logistic regression analysis was used to test the independent association between PHR with MetS and metabolic overweight/obesity phenotypes. In addition, we performed smooth curve fitting and subgroup analyses. Results Logistic regression analysis, after adjusting for covariates, indicated that each 10-unit increase in PHR was associated with elevated risks of MetS (OR = 1.29, 95% CI: 1.24–1.35). There was a significant positive association between PHR and the occurrence of both MHO (OR = 1.15, 95% CI: 1.11–1.19) and MUO (OR = 1.16, 95% CI: 1.12–1.20), while the association with MUNW remained unclear (P = 0.73). In addition, we found a nonlinear relationship between PHR and the incidence of MetS, MHO, and MUO. Conclusion PHR demonstrates strong associations with MetS, MHO, and MUO, indicating its potential utility as an early biomarker for metabolic dysfunction.